Abandonment of a Software Process Improvement Program: Insights from Case Studies - Albuquerque, Regina; Santos, Gleison; Malucelli, Andreia; Reinehr, Sheila (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2020: Anais do XIX Simpósio Brasileiro de Qualidade de Software, 2020)
Software processes improvement (SPI) based on maturity models is a well-researched theme regarding aspects such as adoption benefits, process definition, and automated support environments. However, few studies address the reasons that can lead an organization to abandon SPI. It is vital for organizations that seek to improve their processes to know what can negatively influence SPI and, thus, take actions to mitigate the risk of SPI failure, avoiding the loss of effort in the implementation stage. We present a study's results to understand how abandonment occurs in software process improvement programs after successful assessments based on maturity models. We conducted case studies in four Brazilian software companies. The results show that SPI initiatives failed because of both internal factors (people, SPI project management, organizational aspects, and processes) and external factors (country economic crisis, outsourcing, and governmental political influence) to the organizational context.